Pearl Millet Genetic Traits Shape Rhizobacterial Diversity and Modulate Rhizosphere Aggregation - Ndour, Papa M. S.; Gueye, Mariama; Barakat, Mohamed; Ortet, Philippe; Bertrand-Huleux, Marie; Pablo, Anne-Laure; Dezette, Damien; Chapuis-Lardy, Lydie; Assigbetsé, Komi; Kane, Ndjido Ardo; Vigouroux, Yves; Achouak, Wafa; et al. (Frontiers in Plant Science, 2017)
Root exudation contributes to soil carbon allocation and also to microbial C and energy supply, which subsequently impacts soil aggregation around roots. Biologically-driven soil structuration is an important driver of soil fertility. Plant genetic determinants of exudation and more generally of factors promoting rhizosphere soil aggregation are largely unknown. Here, we characterized rhizosphere aggregation in a panel of 86 pearl millet inbred lines using a ratio of root-adhering soil dry mass per root tissue dry mass (RAS/RT). This ratio showed significant variations between lines, with a roughly two fold amplitude between lowest and highest average values. For 9 lines with contrasting aggregation properties, we then compared the bacterial diversity and composition in root-adhering soil. Bacterial α-diversity metrics decreased with the “RAS/RT ratio”. Regarding taxonomic composition, the Rhizobiales were stimulated in lines showing high aggregation level whereas Bacillales were more abundant in lines with low ratio. 184 strains of cultivable exopolysaccharides-producing bacteria have been isolated from the rhizosphere of some lines, including members from Rhizobiales and Bacillales. However, at this stage, we could not find a correlation between abundance of EPS-producing species orthologs in bacterial communities and the ratio RAS/RT. These results illustrated the impact of cereals genetic trait variation on soil physical properties and microbial diversity. This opens the possibility of considering plant breeding to help management of soil carbon content and physical characteristics through carbon rhizodeposition in soil.